Determinants of Low Political Participation among Indigenous People in Malaysia: A Systematic Literature Review - Sabtu, Muhamad Helmy; Abdul Razzaq, Abdul Rasid; Razali, Nurul Aimi; Md Nor, Noranifitri; Md Ramlan, Saiful Farisin; Abdul Halim, Shah Mohd Akmal (Journal of Social Transformation and Regional Development, 2026)
Orang Asli and other Indigenous peoples of Malaysia, including native communities in Sabah and Sarawak, represent minority populations historically marginalized in political, economic, and social domains. While Malaysia has introduced inclusive policies since independence to improve access to development, Indigenous political representation and engagement remain disproportionately low. This review aims to assess the nature, patterns, barriers, and enablers of political participation among Indigenous peoples in Malaysia over the last two decades. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines were used to conduct this systematic review. The research question was framed using the Population, Phenomenon of Interest, Context, and Outcome (PICO) framework. Comprehensive searches were conducted across Scopus, Web of Science, EBSCOhost, PubMed, ProQuest, Google Scholar, MyJurnal, and MyCite databases. The screening and selection process identified 8 relevant studies published between 2000 and 2025. These studies were appraised using the Mixed Methods Appraisal Tool (MMAT) for methodological quality. The included literature focused on Orang Asli in Peninsular Malaysia (5 studies), Indigenous youth participation (2 studies), and cross-regional comparisons including Sabah and Sarawak (1 study). Four primary themes emerged: legal-institutional barriers to participation, lack of political education, marginalization in mainstream electoral processes, and emerging Indigenous-led activism. Despite policy advancements, Indigenous political participation remains limited by structural discrimination, inadequate representation, and mistrust in political institutions. However, an emerging trend in youth-led movements and community empowerment initiatives presents a promising shift. There is a critical need for targeted civic education, legislative reform, and meaningful inclusion of Indigenous voices in decision-making processes to improve democratic participation and Indigenous sovereignty in Malaysia.